Translation or Intertextuality: A Literature Comparative Analysis of “The Young Dead Soldiers Do Not Speak” by Archibald MacLeish and “Krawang Bekasi” by Chairil Anwar - Rahman, Fakhriawan Fathu; Rahman, Fathu (Elsya : Journal of English Language Studies, 2019)
This study aims to pinpoint the relevant relation between two literary works which have a relationship with one another in the perspective of comparative literature studies. Data were gathered through the text deconstruction theory method by means of an intertextuality approach. The method is applied to juxtapose two well-known poems, Krawang Bekasi (Indonesia) and The Young Dead Soldiers Do Not Speak (America), which are suspected of having the same content and theme, but their relations were never revealed. This thematic-based study uses a multicultural perspective and is naturally suitable for comparative literature study. The objective of this study was to reveal the existence of Krawang Bekasi as one of the Indonesian poems written by Chairil Anwar and to demonstrate the cultural translation methods, known as cultural intertexts relation, for finding the intertextuality of two literary works. In fact, by tabling line through line, the intertextuality was found to be workable in comparative literature. As a result, the study shows that Krawang Bekasi by Chairil Anwar is an adaptation which borrows from and transforms The Young Dead Soldiers Do Not Speak by Archibald MacLeish. Thus, the intertextual relationship of these two works is revealed.